2009
DOI: 10.1007/s12237-009-9157-9
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Phytoplankton Do Not Rest in Winter

Abstract: The climatology and interannual variability of winter phytoplankton was analyzed at the Long Term Ecological Research Station MareChiara (LTER-MC, Gulf of Naples, Mediterranean Sea) using data collected from 1985 to 2006. Background winter chlorophyll values (0.2-0.5 μg chl a dm −3 ) were associated with the dominance of flagellates, dinoflagellates, and coccolithophores. Winter biomass increases (<5.47 μg chl a dm −3 ) were often recorded until 2000, generally in association with lowsalinity surface waters (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 66 publications
(80 reference statements)
3
51
1
Order By: Relevance
“…Nevertheless, the observation that, in the Bay of Calvi, mesozooplankton biomass collected weekly between January and April was 2-fold lower in 2006 and 2008 than in 2010 (Collignon, 2014) suggests that phytoplankton was not strongly controlled by grazers during the cold-water periods. This is in agreement with several studies reporting that grazing is low in the Western Mediterranean in winter in both coastal areas (Duarte et al, 1999;Agustí and Duarte, 2000;Zingone et al, 2010) and the open sea (Auger et al, 2014). Moreover, Behrenfeld (2010) showed that vertical mixing, which is essential for phytoplankton bloom formation, dilutes both predators and preys, whereas stratified conditions concentrate them.…”
Section: Interannual Control Of Phytoplankton Bloomssupporting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, the observation that, in the Bay of Calvi, mesozooplankton biomass collected weekly between January and April was 2-fold lower in 2006 and 2008 than in 2010 (Collignon, 2014) suggests that phytoplankton was not strongly controlled by grazers during the cold-water periods. This is in agreement with several studies reporting that grazing is low in the Western Mediterranean in winter in both coastal areas (Duarte et al, 1999;Agustí and Duarte, 2000;Zingone et al, 2010) and the open sea (Auger et al, 2014). Moreover, Behrenfeld (2010) showed that vertical mixing, which is essential for phytoplankton bloom formation, dilutes both predators and preys, whereas stratified conditions concentrate them.…”
Section: Interannual Control Of Phytoplankton Bloomssupporting
confidence: 92%
“…However, our hypothesis is grounded in both the robustness of the very detailed 1999 data series, and the fact that, in the available 15 Tchl a time series at station PHYTOCLY, the phytoplankton bloom always occurred within the cold-water period. A few field studies have also reported the regular occurrence of winter blooms in vertically mixed coastal Mediterranean waters (Ribera d 'Alcalà et al, 2004;Goffart and Hecq, 2005;Zingone et al, 2010). According to the latter study, those blooms are characterised by moderate chl a concentrations vertically distributed down to the bottom, which result in winter depth-integrated biomass values that are comparable to those found in spring at the same station.…”
Section: Specific Aspects Of the Phytoplankton Bloom In The Bay Of Calvimentioning
confidence: 78%
See 3 more Smart Citations